The Influence of Green Infrastructure and Community Participation on Sustainable Natural Resource Management in Indonesia - Darman Darman; Hans Yohanes Elrix Doirebo (West Science Social and Humanities Studies, 2024)
This research explores the influence of green infrastructure and community participation on sustainable natural resource management in Indonesia through qualitative analysis. Fifteen stakeholders, including government officials, activists, community leaders, NGO representatives, and scholars, were interviewed to gather diverse perspectives on the subject. Thematic analysis revealed key themes highlighting the critical role of green infrastructure in enhancing ecosystem resilience and biodiversity conservation. Additionally, community participation emerged as essential for fostering inclusive decision-making processes and empowering local communities in resource governance. Despite challenges such as funding constraints and power imbalances, opportunities for innovation and collaboration were identified. The findings underscore the interconnectedness of green infrastructure, community participation, and sustainable natural resource management, suggesting integrated approaches for addressing the complex challenges facing Indonesia's natural resources.